Using of digital instrumentation equipment for experimental researches of track and rolling stock interaction - Bondarenko, I. O.; Kurgan, D. M.; Patlasov, O. M.; Savluk, V. Ye. (Science and Transport Progress, 2011)
The tendencies of application of modern digital technique for carrying out the experimental research of the rolling stock effect on the track are shown. The possibility of determination of the elasticity module of the basis under a rail by results of measurements of stresses in rails is considered.